2004
DOI: 10.1038/sj.npp.1300522
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the CS- and US-Pre-Exposure Effects in the Conditioned Taste Aversion Paradigm and Their Abolition Following Systemic Amphetamine Treatment in C57BL6/J Mice

Abstract: In classical conditioning, pre-exposures to either the to-be-conditioned stimulus (CS) or unconditioned stimulus (US) can retard subsequent conditioning between the CS and US. The present experiment evaluated the expression of these two pre-exposure effects in mice of the C57BL6/J strain, one of the most common background strains for genetically altered mice. We tested whether their expression would be disrupted by amphetamine treatment (2.5 mg/kg, i.p.) in a conditioned taste aversion paradigm with sucrose as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 54 publications
4
30
2
Order By: Relevance
“…A key objective in this study is to test whether the same amphetamine treatment regime would also lead to the attenuation or abolition of the USPEE-namely, the retardation in active avoidance performance seen in animals having been repeatedly pre-exposed to the shock US. A positive outcome in this direction would be in keeping with the finding reported by Meyer et al (2004) in the CTA paradigm. However, our previous experience (e.g.…”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…A key objective in this study is to test whether the same amphetamine treatment regime would also lead to the attenuation or abolition of the USPEE-namely, the retardation in active avoidance performance seen in animals having been repeatedly pre-exposed to the shock US. A positive outcome in this direction would be in keeping with the finding reported by Meyer et al (2004) in the CTA paradigm. However, our previous experience (e.g.…”
Section: Introductionsupporting
confidence: 83%
“…Recently, we have shown that LI and the USPEE are similarly abolished by systemic amphetamine (2.5 mg/kg, i. p.) in mice using a conditioned taste aversion (CTA) paradigm in which the animals learned to associate a flavored liquid with gastric malaise (Meyer et al 2004). The present study is designed to test the generality of this parallelism by extension to another associative learning paradigm, namely active avoidance learning, in the same species.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations